2017
DOI: 10.1111/eip.12443
|View full text |Cite
|
Sign up to set email alerts
|

Research and practice for ultra‐high risk for psychosis: A national survey of early intervention in psychosis services in England

Abstract: Despite clear evidence for the benefit of early intervention in this population, current provision for UHR within EIP services in England does not match clinical guidelines. While some argue this is due to a lack of allocated funding, it is important to note the similar variable adherence to clinical guidelines in the treatment of people with established schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…We note the UHR phase represents a unique opportunity to intervene to prevent future ill‐health (Carney et al, , ). The review by Stain et al () showing that a high number of UHR services utilize antipsychotic medication strengthens our argument that there is a failed opportunity to prevent serious physical health problems in an already vulnerable group.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…We note the UHR phase represents a unique opportunity to intervene to prevent future ill‐health (Carney et al, , ). The review by Stain et al () showing that a high number of UHR services utilize antipsychotic medication strengthens our argument that there is a failed opportunity to prevent serious physical health problems in an already vulnerable group.…”
supporting
confidence: 67%
“…
We read with interest the paper by Stain, Mawn, Common, Pilton, and Thompson (2017) published online for "Early Intervention in Psychiatry." The paper provides important findings and carries implications for future service development.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent appraisal of the standard confirmed that it is unclear how adopting the recommended extended age range and treating CHR-P cases could impact on the positive outcomes already associated with 14 to 35 years age range (40). A further independent survey of CHR-P services in the UK concluded that current provision for CHR-P in England does not match clinical guidelines (41). Fourth, concerning illicit substance misuse, only a minority of CHR-P individuals reported using them.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the International Early Psychosis Association recommendations that interventions are provided flexibly and in low stigmatising environments, sessions are held in the patient's home or local health service clinic. 54 At the final session, participants will be asked to complete a self-report questionnaire to assess the acceptability of the intervention (AARP 55 ).…”
Section: The Sleepwell Interventionmentioning
confidence: 99%